Analysing stereotypical food consumption behaviours: ‘This way up?’ Is there really a ‘right’ way to eat a biscuit? - Charles Spence (Intellect, 2021)
Many of the mundane foods that we eat on an everyday basis are consumed in a manner that may be considered stereotypical, conventional, habitual or, on occasion, even a playful ritual. There are a number of reasons for such behaviours, and the potential benefits for the consumer are discussed in the case of vertically asymmetrical foods where the upper and lower surfaces differ. Maximizing the eye appeal of the food product, maximizing the multisensory flavour experience and the ubiquitous benefits of ritual to the enjoyment of consumption experiences are all put forward as possible explanations for such behaviours in this opinion piece. Ultimately, however, the paucity of empirical evidence concerning the influence of the manner of eating such ubiquitous foods (right way-up or upside-down) on the multisensory tasting experience is highlighted. This is a seemingly important lacuna in the food science literature, given the multiple competing explanations concerning how such experiences might be affected, if at all, that suggest themselves. Looking to the future, it would clearly be of great interest, given the growing global obesity crisis, to understand whether it might be possible to increase sensory enjoyment and/or satiety by the better/optimized design of foods and/or food consumption behaviours.